Liver burst from blunt trauma of abdomen due to hunting gun trigger - Guerrero Pere, Omar P; Sierra, Atanasio J (Cirugía del Uruguay, 2020)
An exceptional case of stellate burst of the liver left lobe by a contusion mechanism caused by a gunshot, with no bullet penetration and spared skin, .is reported upon. The circumstances underlying this rare occurrence are discussed.